SEBARAN BASIS HUTAN RAKYAT DI KABUPATEN PANGANDARAN PROVINSI JAWA BARAT - Suhartono Suhartono (Fakultas Kehutanan Universitas Mulawarman, 2020)
The Pangandaran Regency's forestry sector has the potential to be a driving force in regional economic development. However, the development of the forestry sector, especially private forest, has not yet focused on locations of private forest bases so the utilization of available resource potentials has not been optimal so that an appropriate strategy is needed for its development. This study aims to determine the base of private forest in the Pangandaran Regency that potential to support regional economic development. The method used in this study is a desk study by utilizing secondary data on private forest area and area size in the Pangandaran Regency, which is published by the Central Statistics Agency. Data analysis was performed descriptively using the Location Quotient method approach to determine the areas that were the basis or non-basis of private forest. The results showed that 4 of 10 subdistricts in the Pangandaran Regency were included in the category of private forest base and could be a priority scale in development including Cigugur Subdistrict, Parigi Subdistrict, Sidamulih Subdistrict and Pangandaran Subdistrict with LQ value of 3.21; 1.78; 1.08 and 1.03